Mengoptimalkan Proses Bisnis Melalui Pengelolaan Referensi dan Master Data Manajemen - Shaqina, Maheza; Nasution, Muhammad Irwan Padli (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Managing reference and master data has become one of the most important challenges to support business efficiency in the digital age. This study explores how effective data management can improve decision-making and add value. The methodology employed includes a literature review and descriptive analysis of the cases studied. The findings indicate that structured data management can enhance integrity, reduce duplication, and accelerate operational processes.